Effects of copper on larvae of the marbled crab Pachygrapsus marmoratus (Decapoda, Grapsidae): toxicity test and biochemical marker responses - Oliva, M. (2019)
The importance of trace elements in ecotoxicological investigations is a well-known issue when monitoring polluted areas such as commercial harbors. Copper represents one of the most common metal contaminants, often detected in these areas as it is widely employed in various fields and has many sources of inflow in the marine environment. Pachygrapsus marmoratus is a widespread intertidal crab species that has been extensively studied in ecology, ethology and population genetics. Ecotoxicological studies have also been performed, exclusively on the adult stage. In the present study we investigated the mortality and biochemical (oxidative stress and neurotoxicity) responses of P. marmoratus larvae exposure to environmental relevant concentration of copper. Results showed dose-dependent responses in terms of larval mortality, with a calculated LC50 value of 0.5 mg/L of Cu2+. The LC50 concentration was used as the starting point for subsequent biochemical response evaluation. Results also demonstrated dose-dependent activation of antioxidant systems assuming a compensatory antioxidant activity to prevent higher cellular damage when larvae were exposed to the highest concentrations of copper. Moreover, a significant enhancement of neurotransmitter activities was observed, assuming a possible direct interaction of copper with the enzymes or an increase of free copper ion aliquot into the cells.